Corruption, Taxes and Compliance - Baum, Anja (IMF Working Papers; Working Paper ;, 2017)
This paper revisits the effects of corruption on the state's capacity to raise revenue, building on the existing empirical literature using new and more disaggregated data. We use a comprehensive dataset for 147 countries spanning 1995-2014, compiled by the IMF. It finds that-consistent with the existing literature-corruption is negatively associated with overall tax revenue, and most of its components. This relationship is predominantly influenced by the way corruption interacts with tax compliance. The establishment of large taxpayer offices improves tax compliance by dampening the perception of corruption, thereby boosting revenue.